2007
DOI: 10.1021/ie061167p
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Chloride from Acidic Solutions Using NO2

Abstract: Chloride (Cl -) salt processing in strong acids is used to recycle plutonium (Pu) from pyrochemical residues. The Savannah River National Laboratory (SRNL) is studying the potential application of nitrogen dioxide (NO 2 ) gas to effectively convert dissolved pyrochemical salt solutions to chloride-free solutions and improve recovery operations. An NO 2 sparge has been shown to effectively remove Cl -from solutions containing 6-8 M acid (H + ) and up to 5 M Cl -. Chloride removal occurs as a result of the compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Recent research performed at the Savannah River National Laboratory in South Carolina revealed that chloride can be effectively oxidized to chlorine gas in nitric acid using nitrogen dioxide [33]. The experiments were performed at various hydrochloric/nitric acid concentrations to determine whether chloride was removed from acid solutions due to the nature of the strong acid or due to the use of nitrogen dioxide gas sparging.…”
Section: Methods 4: Chloride Ion Eliminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research performed at the Savannah River National Laboratory in South Carolina revealed that chloride can be effectively oxidized to chlorine gas in nitric acid using nitrogen dioxide [33]. The experiments were performed at various hydrochloric/nitric acid concentrations to determine whether chloride was removed from acid solutions due to the nature of the strong acid or due to the use of nitrogen dioxide gas sparging.…”
Section: Methods 4: Chloride Ion Eliminationmentioning
confidence: 99%
“…Nitrosyl chloride gas was the dominant gas produced when the acid strength of the solution was below 4 M. However, nitrosyl chloride gas could only be produced when a constant flow of nitrogen dioxide was sparged through the solution. For acid concentrations ranging from 5-10 M the dominant gas produced was chlorine gas [33]. Again, this reaction required a constant flow of nitrogen dioxide through the solution.…”
Section: Methods 4: Chloride Ion Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Under industrial conditions, concentration of chloride ions in nitric acid can reach 1 mol L -1 [9,10] whereas for the dechlorination process the final concentration should be lower than 10 -3 mol L -1 to avoid AgCl precipitation when AgNO 3 is introduced. The rate of reaction (1) may be controlled by charge transfer or mass transport depending on the applied current density, chloride concentration, and hydrodynamic conditions which may depend on the rate of gas evolution at the anode [11].…”
Section: Mass Transfer Ratementioning
confidence: 99%
“…Although a chemical process of chloride removal from pyrochemical residues by sparging nitrogen dioxide in the solution was proposed by Pierce et al [9], the implementation of an electrochemical process involving direct chloride oxidation can be considered as a simpler technique [8,10]:…”
Section: Introductionmentioning
confidence: 99%